Pemikiran al-Ghazali dalam Pengembangan Kurikulum Pendidikan Agama Islam di Era Digital - Ike Widyastuti; Dartim Dartim (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This paper analyzes the contribution of Imam al-Ghazali’s thoughts to the development of the Islamic Education curriculum in the digital era. In the context of complex digitalization, Islamic education plays a crucial role in shaping individuals who are intelligent, knowledgeable, and understand religious values. Al-Ghazali emphasizes the integration of worldly and spiritual knowledge as well as the importance of applying knowledge in daily life. This research employs a qualitative approach through literature review to analyze various relevant sources. The findings indicate that al-Ghzali’s educational concepts are highly relevant to contemporary educational challenges, offering a comprehensive framework for designing a curriculum that not only imparts knowledge but also instill moral values. By integrating cognitive, affective, and psychomotor aspects, the proposed curriculum aims to create individuals who are not only academically intellegent but also possess a high sense of social responsibility, along with a personality that is faithful, devout, and ethical. The contributions of al-Ghazali’s thoughts provide a foundation for developing a relevant and meaningful Islamic education curriculum in today’s multicultural society.